PENYETARAAN TES UAN: MENGAPA DAN BAGAIMANA? - SukimoDS, SukimoDS (LPMPP Universitas Negeri Yogyakarta, 2008)
Debates concerningwhat is right and what is wrOng with national finalexamination (UAN) in Indonesiaare not new. National Final Examination (UAN),a significant processusing a test form to measure learning output, has beendeveloped to provide useful information for the decision makers (parents,educators,policy